Benign breast pathology in general practice. Issue 11 (November 2022) - van der Zanden, Eleanor; Cooper, Max; Sornalingam, Sangeetha; Zammit, Charles
Many thousands of patients present each year to general practice with breast symptoms. Patients are often concerned that their symptoms might indicate cancer; however, the majority represent benign breast disease. On average, a full-time GP will diagnose one or two cases of breast cancer a year. It can be difficult to distinguish between potentially malignant and benign conditions in the GP setting, as well as manage patient anxiety and expectations. This article aims to cover pathology, diagnosis and management of benign breast disease and improve conﬁdence in managing patients diagnosed with benign disease. The article will not cover the topics of breast cancer or breast pathology in pregnancy and male patients.